Function and Regulation of Histone H3 Lysine-4 Methylation During Oocyte Meiosis and Maternal-to-Zygotic Transition - Sha, Qian-Qian; Zhang, Jue; Fan, Heng-Yu (Frontiers in Cell and Developmental Biology, 2020)
During oogenesis and fertilization, histone lysine methyltransferases (KMTs) and histone lysine demethylases (KDMs) tightly regulate the methylation of histone H3 on lysine-4 (H3K4me) by adding and removing methyl groups, respectively. Female germline-specific conditional knockout approaches that abolish the maternal store of target mRNAs and proteins are used to examine the functions of H3K4 KMTs and KDMs during oogenesis and early embryogenesis. In this review, we discuss the recent advances in information regarding the deposition and removal of histone H3K4 methylations, as well as their functional roles in sculpting and poising the oocytic and zygotic genomes. We start by describing the role of KMTs in establishing H3K4 methylation patterns in oocytes and the impact of H3K4 methylation on oocyte maturation and competence to undergo MZT. We then introduce the latest information regarding H3K4 demethylases that account for the dynamic changes in H3K4 modification levels during development and finish the review by specifying important unanswered questions in this research field along with promising future directions for H3K4-related epigenetic studies.